Auditor’s Ability in Detecting Fraud - Khomsiyah, Khomsiyah; Wilson, Jetri; Dwi Mulyani, Susi (Opción, 2019)
The purpose of this study is to examine the ability of auditor to detect fraud. The variables of professional scepticism, communication skill, Computer Assisted Auditing Techniques (CAATs), and certification of forensic auditor predicted influence on the auditor’s ability to detect fraud. The study used primary data obtained using questionnaire instrument. The sample used in the study was 160 respondents who were the auditors of the auditor board (BPK). Multiple linear regression analysis used to test the effect of indepen- dence variables on the auditor’s ability to detect fraud. The study results confirmed that professional scepticism, communication skill, Computer Assisted Audit Techniques (CAATs), and forensic auditor certification have positive effect on auditor’s ability to detect fraud. The implications of this study are to strengthen the importance of professional scepticism, communication skill, Computer Assisted Auditing Techniques (CAATs), and forensic auditor certification for auditors in fraud detection efforts.